Chemotherapy‐Mediated Induction of PD‐L1 via SEI1 Facilitates Myeloma Immune Evasion - Rui Chen; Zongwei Li; Zhihong Fang; Zou Li; Daoyan Yang; Yuan Li; Shurong Liu; Zhiqiang Liu; Rui Liu; Huan Liu (Advanced Science)
Abstract Multiple myeloma (MM) is a plasma cell‐derived malignancy. While immune checkpoint blockade immunotherapy has advanced myeloma treatment, chemotherapy remains the primary therapy. How chemotherapy interacts with immune checkpoint expression and impacts immunotherapy efficacy remains unclear. Here it is discovered that chemotherapeutic drugs induce DNA damage and activate the cyclic guanosine monophosphate (GMP)–adenosine monophosphate (AMP) synthase (cGAS)/stimulator of interferon genes (STING) signaling pathway. This activation promotes phosphorylation of the interferon regulatory factor 7 (IRF7), which binds to the promoter region of SERTA‐containing domain 1 (SERTAD1, also called SEI1) gene to enhance its transcription. The SEI1 directly interacts with the enhancer factors CREB‐binding protein (CBP)/p300 and RNA polymerase II (pol II)‐associated factor 1 (PAF1) complex, promoting transcriptional activity and leading to upregulation of programmed death ligand‐1 (PD‐L1) and immune escape in myeloma. Both in vitro and in vivo experiments demonstrate that treating myeloma cells with PD‐L1 antibodies post‐chemotherapy significantly enhances the killing efficiency of activated T cells, compared to sequential treatment with chemotherapy and PD‐L1 antibodies. This research not only uncovers a pivotal regulatory mechanism of PD‐L1 upregulation but also provides a compelling rationale for the integration of chemotherapy and immunotherapy in myeloma treatment.